Journalism Training to Improve Political Literacy for Muhammadiyah Leuwiliang Students - Mulkan Habibi; Hiru Muhammad; Hari Eko Purwanto; Lutfi Lutfi; Alfareji Febrian; Hafsya Abida (Universitas Lambung Mangkurat, 2024)
People who lack political literacy and are not wise when using communication media are often trapped by the flow of wrong information. So, literacy or education about journalism must be carried out from the early generations. Those who are still students need to prepare themselves from the start to be able to understand the quality of the various information they receive, including political information. This community service aims to provide understanding and increase journalistic literacy for Muhammadiyah students who are members of the Leuwiliang Muhammadiyah Student Association organization in Bogor Regency, West Java. Community Service Method using approach Participatory Action Research (PAR) carried out in the form of socialization and assistance to Muhammadiyah Leuwiliang students carried out in several stages, including mapping the conditions of problems faced by partners, preparing training program steps, preparing the division of tasks for each service team, and then carrying out training in the form of providing journalistic material and various types of hoax information, which is usually spread through various social media platforms. The results of community service conclude that students need a variety of information or a collection of data or facts that can be managed into something useful for the recipient. Muhammadiyah students need information that supports various processes such as education, political participation, and Muhammadiyah's missionary needs.